Comparison of extraction methods of chitin from ganoderma lucidum mushroom obtained in submerged culture (2014)
ABSTRACT: The chitin was isolated from the Ganoderma lucidum submerged cultures mycelium as potential source of chitin under biotechnological processes. The extraction of chitin was carried out through 5 different assays which involved mainly three phases: pulverization of the mushroom, deproteinization of the mycelia with NaOH solution, and a process of decolorization with potassium permanganate and oxalic acid. The chitin contents extracted from 9-day mycelia were 413, 339, 87, 78, and 144 mg/g−1 (milligrams of chitin/grams of dry biomass) for A1, A2, A3, A4, and A5, respectively. Obtained chitin was characterized by X-Ray Diffraction (XRD), by Fourier transform infrared spectroscopy (FTIR), and by thermal analysis (TGA). The results showed that Ganoderma lucidum chitin has similar characteristic of chitin from different fonts. The advantage of the biotechnological processes and the fact that Ganoderma lucidum fungus may be used as a potential raw material for chitin production were demonstrated.